Corpos dissidentes e insistentes: pessoas negras com deficiência no município de Sorocaba e o Sistema único de assistência social - Costa, Walkiria Santos (Universidade Federal de São Carlos, 2025)
This dissertation critically analyzes the performance of the Unified Social Assistance System (SUAS) regarding Black people with disabilities in the city of Sorocaba, São Paulo, considering the intersections of race, disability, and social class. Grounded in intersectional theory, the research aims to move beyond the isolated view of disability and reveals how the capitalist social structure produces and reproduces inequalities affecting these subjects. Starting with the 1988 Federal Constitution and the active participation of the disability rights movement during the constituent process, this study discusses the contradictions in the implementation of the National Social Assistance Policy (PNAS) and the Brazilian Inclusion Law (LBI). The methodology includes bibliographic, documentary, and field research, with semi-structured interviews conducted with SUAS professionals and users, emphasizing active listening and the protagonism of the subjects involved. The analyzed data show gaps in policy implementation, persistent tutelary practices, and the invisibility of racial markers in service provision. The study concludes that SUAS, in its current structure, still lacks effective mechanisms to address the multiple oppressions experienced by Black people with disabilities. There is an urgent need for anti-racist, anti-ableist, and intersectional approaches in social assistance services.
Dissident and insistent bodies: black people with disabilities in the municipality of Sorocaba and the unified social assistance system
Keywords: Política Pública; Raça; Interseccionalidade; Assistência Social; Deficiência; Disability; Race; Intersectionality; CIENCIAS SOCIAIS APLICADAS::SERVICO SOCIAL; 10. Redução das Desigualdades; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável